How to Define Successful Stocking of Florida’s Freshwater Recreational Fisheries - Edward Vincent Camp; Rick Stout; Nick Trippel; Jon Fury; Stasey Whichel; Kai Lorenzen (EDIS)
Florida researchers and fisheries management agencies have conducted years of research on stocking, a common and popular but intensive option for improving recreational fisheries, but determining how successful it has been in Florida has been challenging. This 7-page fact sheet written by Edward V. Camp, Rick Stout, Nick Trippel, Jon Fury, Stasey Whichel, and Kai Lorenzen and published by the UF/IFAS School of Forest Resources and Conservation Program in Fisheries and Aquatic Sciences reviews recent scientific literature to describe the benefits of stocking and the potential drawbacks to create useful definitions of stocking success, as well as metrics for evaluation that are specifically tailored for Florida. Well-planned stocking can not only improve recreational fishing but achieve broader research and management goals and help us to understand how fisheries function, both biologically and socioeconomically. http://edis.ifas.ufl.edu/fa216